Visualization of chikungunya virus infection in vitro and in vivo. Issue 1 (1st January 2019) - Zhang, Hong-Lei; Dong, Hao-Long; Zhang, Ya-Nan; Xu, Lin-Lin; Deng, Cheng-Lin; Li, Xiao-Feng; Li, Xiao-Dan; Ye, Han-Qing; Yuan, Zhi-Ming; Qin, Cheng-Feng; Zhang, Bo
ABSTRACT: Chikungunya virus (CHIKV), a mosquito-borne alphavirus, has become an important re-emerging pathogen with its rapid spread to many non-endemic areas. The lack of effective vaccines and antiviral agents is largely attributed to the elusive infection and dissemination dynamics in vivo . In this study, we designed and developed a novel, replication-competent, CHIKV reporter virus (CHIKV-iRFP) encoding a near infrared fluorescent protein (iRFP). In vitro and in vivo characterization demonstrated that CHIKV-iRFP retained similar replication and virulence phenotypes to its parental virus. Neonatal BABL/c mice and IFNAR −/− A129 mice were highly susceptible to CHIKV-iRFP infection. Following intracranial (i.c.) inoculation, CHIKV-iRFP efficiently replicated and disseminated into whole body, resulting in rapid death in an age-dependent manner. Remarkably, upon footpad injection, CHIKV-iRFP readily disseminated from footpad to head and whole skeleton, with a specific tropism for bone marrow. Taken together, this novel reporter virus provides a powerful tool to track real time CHIKV replication and to test the in vivo efficacy of vaccines and antiviral therapeutics.